2019
DOI: 10.1016/j.apor.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

CFD modelling of a small–scale fixed multi–chamber OWC device

Abstract: Wave Energy Converters (WECs) have excellent potential as a source of renewable energy that is yet to be commercially realised. Recent attention has focused on the installation of Oscillating Water Column (OWC) devices as a part of harbor walls to provide advantages of cost-sharing structures and proximity of power generation facilities to existing infrastructure.In this paper, an incompressible three-dimensional CFD model is constructed to simulate a fixed Multi-Chamber OWC (MC-OWC) device. The CFD model is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In these modeling approaches, the OWC hydrodynamic coefficients are analytically [27,28], numerically [29,30], or experimentally [31,32] determined. Recently, models based on CFD are experiencing a great expansion for analyzing the interaction between incident waves and OWC structures, including the nonlinear and viscous effects [33][34][35][36][37][38]. The aforementioned modeling approaches were applied to study the effect of different design parameters of the primary conversion efficiency.…”
Section: Owc Chamber and Impulse Turbine Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In these modeling approaches, the OWC hydrodynamic coefficients are analytically [27,28], numerically [29,30], or experimentally [31,32] determined. Recently, models based on CFD are experiencing a great expansion for analyzing the interaction between incident waves and OWC structures, including the nonlinear and viscous effects [33][34][35][36][37][38]. The aforementioned modeling approaches were applied to study the effect of different design parameters of the primary conversion efficiency.…”
Section: Owc Chamber and Impulse Turbine Overviewmentioning
confidence: 99%
“…However, a holistic approach is needed, going into the direction of a combined optimization of the converters for specific wave conditions. Indeed, the optimal damping for the OWC chamber depends on its geometry and the local characteristics of the incident wave and, in turn, the performance of the air turbine depends on the pressure difference made available by the chamber [11,35,38,48]. For these reasons, analytical wave-to-wire models are the most suited solution for the primary design of OWC wave energy converters, allowing for investigation of a wide variety of design solutions with the need of reduced computational power and time.…”
Section: Owc Chamber and Impulse Turbine Overviewmentioning
confidence: 99%
“…[33] followed up with an experimental study and observed the existence of two different resonant frequencies corresponding to the inner-and outer-chambers, and concluded that the combination of the two different resonant frequencies of inner and outer chambers lead to a wider frequency region. Shalby et al [34][35] proposed a new type of MC-OWC wave energy device, which has four chambers along the incident wave direction. Numerical 3-D studies with focus on the capture width ratio and free surface elevation were presented.…”
Section: Introductionmentioning
confidence: 99%
“…However, one-dimensional models are unable to give an insight of the different hydrodynamic processes that occur in the proximity of, and inside the U-OWC system. To overcome the intrinsic limits of these one-dimensional models, a numerical approach based on CFD simulations has been proposed by the authors [18,19] and by others (e.g., [20][21][22][23]). The performance of an OWC device under a range of wavelengths for different wave steepness was analyzed by Kamat et al [21] by means of CFD simulations.…”
Section: Introductionmentioning
confidence: 99%